Reasons for not using ecstasy: a qualitative study of non-users, ex-light users and ex-moderate users - Comis Maria; Noto Ana (BMC, 2012)
Abstract Background Although ecstasy is often consumed in the electronic music scene, not everyone with the opportunity to use it chooses to do so. The objective of this study was to understand the reasons for non-use or the cessation of use, which could provide information for public health interventions. Methods A qualitative reference method was used. Our "snowball" sample group consisted of 53 people who were split into three subgroups: non-users (NU, n = 23), ex-light users (EX-L, n = 12) and ex-moderate users (EX-M, n = 18). Individual, semi-structured interviews were conducted, transcribed and subjected to content analysis with the aid of NVivo8. Results Adverse health effects and personal values were given as reasons for non-use in the three groups. Non-users (NU) and ex-light users (EX-L) provided reasons that included fear of possible effects as well as moral, family and religious objections. Ex-moderate users (EX-M) cited reasons related to health complications and concomitant withdrawal from the electronic music scene. However, most of the ex-moderate users did not rule out the possibility of future use. Conclusions Potential effects and undesirable consequences appear to guide the decisions within the different groups. Prevention might target these motivations. Individuals who have used ecstasy indicate that social and environmental factors are the most important factors.